Jesienny panair w Wyrbicy – święto w społeczności wieloetnicznej - Kijewska, Anna (Zeszyty Wiejskie, 2010)
The article describes the local multiethnic community during their annual festival – panair – a big autumn fair taking place in the central village of municipality Varbitsa in north-eastern Bulgaria. In this region a religion is not the main characteristic of people's identity. There are several ethnic groups adhering to Islam (Turkish people, Gypsies, Bulgarian Muslims, Bektashi, Tatars) and Christianity (Bulgarians, Gypsies). The author of the article tries to describe the annual panair as a festival which belongs to all of this people, as a common local tradition. All materials come from fieldwork done by Anna Kijewska during 2007-2008.